Community Structure and Ecological Network's Changes of Vaginal Microbiome in Women Right After Delivery - Li, Hongping; Jiang, Jingbo; Nie, Chuan; Xiao, Bin; Li, Qingxia; Yu, Jieyang (Frontiers in Pediatrics, 2022)
Objectives: Vaginal microbiota is not only an important source of bacterial coloniza-tion for neonates, but also plays a crucial role in maternal and neonatal health. This study aimed to investigate the vaginal microbial community structure right after de-livery and its impact on the neonatal oral microbiome. Methods: In this study, 27 women were recruited from Bao an Maternal and Child Health Hospital. Bacterial compositions of vaginal samples before and right after de-livery, neonatal oral samples right after birth were investigated using 16S rRNA se-quencing of V3-V4 hyper-regions. Results: Vaginal microbiome before delivery was dominated by genus Lactobacillus. After delivery, the vaginal microbial community was altered, with significantly de-creased proportion of Lactobacillus, increased alpha diversity and a more diverse ecological network. A large number subjects dominated by Lactobacillus spp. before delivery shifted to CST (community state type) IV after delivery. Additionally, simi-lar changes were observed in the neonatal oral microbiome, and its community pro-file was more close to vaginal samples after delivery than before delivery with prin-cipal coordinates analysis and microbial source tracking analysis. Conclusion: The vaginal microbiome was altered right after delivery, and impacted the colonization of the neonatal oral microbiome in China. In further, it is vital to understand the longitudinal influence on maternal and neonatal health of vaginal mi-crobiome community changes after delivery.